2023
DOI: 10.1001/jamacardio.2023.1729
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Atherosclerotic Plaque Activity and Future Coronary Events

Abstract: ImportanceRecurrent coronary events in patients with recent myocardial infarction remain a major clinical problem. Noninvasive measures of coronary atherosclerotic disease activity have the potential to identify individuals at greatest risk.ObjectiveTo assess whether coronary atherosclerotic plaque activity as assessed by noninvasive imaging is associated with recurrent coronary events in patients with myocardial infarction.Design, Setting, and ParticipantsThis prospective, longitudinal, international multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…We have demonstrated the feasibility of using coronary 18 F-sodium fluoride to add incremental value to traditional risk prediction scores in patients at very high risk of plaque rupture . By performing hybrid contrast enhanced coronary CT angiography in our study, we have shown that coronary 18 F-sodium fluoride was associated with an increased risk of cardiac death and nonfatal myocardial infarction after adjustment for internationally endorsed CT parameters (adjusted hazard ratio, 1.78; 95% CI, 1.03-3.06; P = .04).…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…We have demonstrated the feasibility of using coronary 18 F-sodium fluoride to add incremental value to traditional risk prediction scores in patients at very high risk of plaque rupture . By performing hybrid contrast enhanced coronary CT angiography in our study, we have shown that coronary 18 F-sodium fluoride was associated with an increased risk of cardiac death and nonfatal myocardial infarction after adjustment for internationally endorsed CT parameters (adjusted hazard ratio, 1.78; 95% CI, 1.03-3.06; P = .04).…”
mentioning
confidence: 69%
“…In contrast, 18 F-sodium fluoride offers a promising solution to monitor the slow progressive transition from a noncalcified to calcified phenotype noted by intense 18 F-sodium fluoride signals persisting more than 12 months . Unlike the transient vascular signals observed with inflammatory radioligands, there is minimal attenuation of the 18 F-sodium fluoride signal with optimal medical therapy—a potential explanation for why patients with increased coronary 18 F-sodium fluoride remain at increased risk of cardiac death and myocardial infarction in the medium term . To our knowledge, our work represents the first prospective observational cohort using coronary positron emission tomography, but complementary prospective observational studies to discern the predictive ability of radioligands measuring vascular inflammation with 18 F-fluoro-2-deoxyglucose and 68 Ga-DOTATATE are ongoing.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Studies have also demonstrated a correlation between NaF uptake and high-risk morphological features on MRI, such as the presence of a lipid-rich necrotic core, or intraplaque haemorrhage 39 . In addition, there is emerging evidence of a prognostic link between NaF signal on PET and the risk of recurrent disease 40 , where coronary NaF imaging had the ability to predict myocardial infarction and cardiovascular death.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor Moss et al recently published a prospective, international, multicenter longitudinal cohort study of 704 patients with recent myocardial infarction (MI) that investigated whether coronary atherosclerotic plaque activity as assessed by 18 F-sodium fluoride positron emission tomography (PET) and coronary computed tomography (CT) angiography is associated with recurrent coronary events. Their findings suggest that coronary atherosclerotic plaque activity is not associated with cardiac death, nonfatal MI, or revascularization after a minimum 2-year follow-up period.…”
mentioning
confidence: 99%